Propuesta De Implementación De Un Sistema De Gestión De Seguridad Y Salud En El Trabajo Basado En Las Normas Ohsas 18001:2007 En La Municipalidad Distrital De Pacasmayo - Soriano Chuquimango, Luber (2017)
The present work is called "Proposal of Implementation of a System of Management of Occupational Safety and Health based on the OHSAS 18001: 2007 standards in the district municipality of Pacasmayo", proposes a proposal and describes the methodology to be followed to implement a system of management of health and safety in the work and that can be applied in similar companies of the public sector between the main studies realized we have: situational diagnosis, identification of hazards and evaluation of risks faith control, system of management of safety and health in the work , economic and financial evaluation. The situational diagnosis presents studies and results in relation to the 193 established guidelines, indicating the sources of verification that have been used and those that did not reach. Compliance score, which results in 92.78% of these guidelines are not met and 7.22% of the established guidelines are being complied with within the public entity. Hazard identification and risk assessment develops IPER analyzes describing the 9 field areas and 4 administrative offices, finding a greater degree of acceptability criterion in drinking water wells with 10.53% and pumping chambers 10.53%, followed by a 9.21% in the public cleaning collectors, and the other areas presenting a lower criterion of average acceptability less than 7%. Also, the control measures are taken based on the results of the IPERC analyzes, which are focused on reducing the degree of risk in critical areas. The occupational safety and health management system is developed on the basis of OHSAS 18001: 2007, in accordance with the logic of the Deming cycle for continuous improvement: plan, verify and establish improvement initiatives; Finally, the economic evaluation was established, in which the viability of the project to implement the management system in occupational safety and health in the Pacasmayo district municipality was determined, analyzing for this the B / C, which is S /. 1.26.